Bridgeless Isolated CUK Converter Using BLDC Motor - Lokesh, K.; Mercy, E. Latha; Poovizhi, D.; Indhumathi, B. (Journal of Trends in Computer Science and Smart Technology, 2022)
The CUK topology is used to propose three novel rectifiers with single phase AC-DC Power Factor Correction (PFC) without a bridge. When compared to a standard CUK Power Factor Correction rectifier, the lack of enhanced heat control and reduced conduction losses are achieved by using the current flows; there are only two semiconductor switches and one input diode bridge channel throughout each period of the switching cycles. The proposed topologies are made to operate in the mode of discontinuous conduction, resulting in a deciding element of almost unity as well as low input current Harmonic Distortion in total. Additional benefits in Discontinuous Conduction Mode operating includes zero current is switched on in the power switches, and in the output diode, zero current is turned off, as well as simplified control circuitry. The power switch can be turned on or off.